PENGEMBANGAN MODEL ARSITEKTUR TEKNOLOGI INFORMASI DESIGN THINKING UNTUK MENDUKUNG DESA CERDAS DI PABEAN UDIK - Rudhy Purabaya; Anita Muliawati; Widya Cholil; Prihandoko (LPPM UNIVERSITAS BINA INSAN, 2026)
Smart village development has become a key strategy for accelerating digital transformation in village governance, in line with the Indramayu Regency program targeting digital villages across 309 villages. This study aims to identify information technology problems and needs and to develop a smart village information technology architecture model in Pabean Udik Village. It applies a human-centered design thinking approach through five stages—empathize, define, ideate, prototype, and test—with data collected through Focus Group Discussions (FGD), observation, and interviews. The empathize stage mapped problems across five smart village dimensions and confirmed high social readiness. The define stage concluded that the village's current information systems and technology are not yet adequate to support the smart village dimensions. The ideate stage produced a layered IT architecture model comprising eleven modules mapped to five dimensions, aligned with regional policy through a follow-up FGD with regency-level stakeholders and business/industry actors. The prototype stage realized it as a low-fidelity prototype, and the test stage validated it through expert judgment and walkthrough, yielding a